Glucose and Metformin Modulate Human First Trimester Trophoblast Function: a Model and Potential Therapy for Diabetes‐Associated Uteroplacental Insufficiency. (14th November 2014) - Han, Christina S.; Herrin, Melissa A.; Pitruzzello, Mary C.; Mulla, Melissa J.; Werner, Erika F.; Pettker, Christian M.; Flannery, Clare A.; Abrahams, Vikki M.
<x xml:space="preserve">Abstract</x> Problem Diabetes confers an increased risk of preeclampsia, but its pathogenic role in preeclampsia is poorly understood. The objective of this study was to elucidate the effects of excess glucose on trophoblast function and whether any changes could be reversed by metformin. Method of study The human first trimester trophoblast cell line (Sw.71) was treated with glucose at 5, 10, 25, and 50 mm, in the presence and absence of metformin. Trophoblast migration was quantified and supernatant cytokine, chemokine, and angiogenic factors measured. Results Increasing concentrations of glucose significantly increased trophoblast secretion of the inflammatory cytokines/chemokines: IL‐1β, IL‐6, IL‐8, GRO‐α, RANTES, and G‐CSF; significantly increased trophoblast secretion of the anti‐angiogenic factors sFlt‐1 and sEndoglin; and significantly decreased trophoblast migration. Excess glucose‐induced trophoblast IL‐1β production was inhibited by disabling the Nalp3/ASC inflammasome. Metformin partially reduced the glucose‐induced inflammatory response, but had no effect on the anti‐angiogenic or antimigratory response. Conclusion Excess glucose induced a pro‐inflammatory, anti‐angiogenic, and antimigratory state in first trimester trophoblast cells. Glucose‐induced trophoblast IL‐1β secretion was mediated by the inflammasome. Glucose‐induced inflammation was partially reversed by metformin. These findings demonstrate the pleiotropic effects of hyperglycaemia on the trophoblast, providing potential explanations for the strong link between diabetes and preeclampsia.